Profiles of Immune Cell Infiltration in Carotid Artery Atherosclerosis Based on Gene Expression Data - Wang, Long; Gao, Beibei; Wu, Mingyue; Yuan, Wei; Liang, Ping; Huang, Jinyu (Frontiers in Immunology, 2021)
Since immune infiltration is closely associated with the progression and prognosis of atherosclerosis, we aimed to describe the abundance of 24 immune cell types within atherosclerotic tissues. In the present study, we used Immune Cell Abundance Identifier (ImmuCellAI), a web-based tool, to estimate the abundances of 24 immune cells based on microarray profiles of atherosclerotic carotid artery samples for the purpose of analyzing their proportions and the dysregulation of immune cell types within carotid atherosclerosis. We found that atherosclerotic immune cells had a diverse landscape, dominated by T cells and myeloid cells, and that macrophages and dendritic cells (DCs) showed different abundances in normal and atherosclerotic tissues. Moreover, the expression of macrophages was closely related to the level of DCs and exhausted T cell expression, while the expression of T helper type 1 (Th 1) cells was strongly correlated with the expression of T helper type 1 (Th 2) cells and effector memory cells. Our data confirm, for the first time, the distinct profile of infiltrating immune cell subpopulations in atherosclerosis, which may facilitate tailoring individualized immunotherapy for patients.